(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to reveal the impact of training programs on the use of modern technology on developing and raising the level of employee performance, The study adopted the descriptive-analytical approach to reach its conclusions. Data was collected by designing a questionnaire consisting of three axes, which was distributed to a study sample of (37) individuals, After subjecting the questionnaire to analysis via the SPSS program, the study reached a set of key findings, the most important of which were: Training on the use of modern technology provides an opportunity for employees to develop their capabilities and raise their performance level, This development occurs through the acquisition of new skills upon completing the training program, in accordance with the actual training needs, There is a statistically significant effect of training on the development and improvement of employee performance, with the use of modern technology acting as a mediating variable.